Systematic review: the quality of the scientific evidence and conflicts of interest in international inflammatory bowel disease practice guidelines. Issue 10 (2nd April 2013) - Feuerstein, J. D.; Akbari, M.; Gifford, A. E.; Cullen, G.; Leffler, D. A.; Sheth, S. G.; Cheifetz, A. S.
Summary Background Guidelines published by the international gastroenterology societies establish standards of care and seek to improve patient outcomes. Aim We examined inflammatory bowel disease guidelines (IBD) for quality of evidence, methods of grading evidence and conflicts of interest (COI). Methods All 182 guidelines published by the American College of Gastroenterology, American Gastroenterological Association, British Society of Gastroenterology, Canadian Association of Gastroenterology, Crohn's and Colitis Foundation of America and European Crohn's and Colitis Organisation as of 27 September 2012 were reviewed. Nineteen IBD guidelines were found. Results Eighty‐nine per cent (n = 17/19) of the guidelines graded the levels of evidence using seven different systems. Of the 1070 recommendations reviewed, 23% (n = 249) cited level A evidence; 28% (n = 302) level B; 36% (n = 383) level C and 13% (n = 136) level D. The mean age of the guidelines was 4.2 years. In addition, 61% (n = 11/19) of the guidelines failed to comment on COI. All eight articles commenting on COI had conflicts with 81% (n = 92/113) of authors reported an average 11.7 COI. Lastly, there were variations in the recommendations between societies. Conclusions Nearly half the IBD guideline recommendations are based on expert opinion or no evidence. Majority of the guidelines fail to disclose any COI, and when commenting, all have numerous COI. Furthermore, the guidelines are not updated frequently and there is a lack of consensus between societal guidelines. This study highlights the critical need to centralize and redesign the guidelines development process.